Circular dichroism spectroscopy of conformers of (guanine + adenine) repeat strands of DNA - Kejnovská, Iva; Kypr, Jaroslav; Vorlícková, Michaela (Chirality, 2003)
(Guanine+adenine) strands of DNA are known to associate into guanine tetraplexes, homodimerize into parallel or antiparallel duplexes, and fold into a cooperatively melting single strand resembling the protein alpha helix. Using CD spectroscopy and other methods, we studied how this conformational polymorphism depended on the primary structure of DNA. The study showed that d(GGGA)(5) and d(GGA)(7) associated into homoduplexes at low salt or in the presence of LiCl but were prone to guanine tetraplex formation, especially in the presence of KCl. In addition, they yielded essentially the same CD spectrum in the presence of ethanol as observed with the ordered single strand of d(GA)(10). Strands of d(GA)(10), d(GGAA)(5), d(GAA)(7), and d(GAAA)(5) associated into homoduplexes in both LiCl and KCl solutions, but not into guanine tetraplexes. d(GAAA)(5) and d(GAA)(7) further failed to form the single-stranded conformer in aqueous ethanol. Adenine protonation, however, stabilized the single-stranded conformer even in these adenine-rich fragments. The ordered single strands, homoduplexes as well as the guanine tetraplexes, all provided strikingly similar CD spectra, indicating that all of the conformers shared similar base stacking geometries. The increasing adenine content only decreased the conformer thermostability.
Keywords: guanin; Guanine; DNA; Repetitive Sequences, Nucleic Acid; adenin; Circular Dichroism; Adenine; cirkulární dichroismus; repetitivní sekvence nukleových kyselin